Dampak Pengetahuan Dan Inovasi Bisnis Terhadap Kinerja Usaha Mikro Kecil Menengah (UMKM) Dalam Perspektif Syariah - Nurlatifah Nurlatifah; Juhadi Juhadi; Fenny Damayanti Rusmana; Ridla Mutiah; Sukma Aditya (Coopetition : Jurnal Ilmiah Manajemen, 2023)
This research is motivated by MSMEs which have a strategic role in the economy. MSMEs are able to generate new jobs, increase the formation of gross domestic product (GDP), and increase the value of national exports. The goal to be achieved in this study is to determine the impact of business knowledge and innovation on the performance of micro, small and medium enterprises (MSMEs) in a sharia perspective. The research method used in this research is descriptive quantitative. Quantitative analysis of descriptive data was carried out using multiple linear regression analysis. The population of this study were convection entrepreneurs in the Subang Regency area, as many as 107 convection entrepreneurs, where the sampling technique used in this study used saturated sampling. The results of the study were obtained simultaneously and partially, that the business knowledge and innovation of the convection entrepreneurs in Subang Regency had a significant effect on the sustainability variable of the convection business in Subang Regency. To cope with the changes, convection businesses must innovate in their digital media so that sales are not only made through offline sales but also online, so that consumers no longer leave their homes to buy products from convection in Subang district.